A Pilot Study to Explore the Influence of the 'Safety First Assessment Intervention' on the Family Environment. Issue 2 (11th June 2019) - Young, Jennifer; Conrad, Agatha; Mah, Beth
Abstract : The family environment is considered an important influence on a young person's well‐being. The 'Safety First Assessment Intervention' is a model of care that considers and incorporates the importance of family environment when assessing and managing distressed young people. This pilot study explores the influence of the 'Safety First Assessment Intervention' on the family environment of young people referred to Child and Adolescent Mental Health Services. A pre‐ and post‐design was used, with families completing the Family Survey before and after their assessment/intervention. The Family Survey was correlated with a validated measure of family function, the APGAR, and pre‐intervention. Significant changes in multiple dimensions of family environment, including reduced level of distress for the adult, increased level of distress for the young person, improved sense of how the family felt the adult was managing currently, and improved confidence in family communication were found. There was no significant change in how the adult understood their role in helping the young person manage their distress. A thematic analysis showed trends in the current concerns for young people and adults as well as the difficulty young people in distress have in identifying their strengths. This pilot study demonstrates that the 'Safety First Assessment Intervention' can influence the family environment in a positive way and highlights the importance of using a family‐based approach for distressed young people.